(untitled) (Research, Society and Development, 2026)
This study aimed to describe the knowledge of undergraduate students from different courses regarding the work of physiotherapists. To this end, a cross-sectional study with a quantitative and qualitative approach was conducted at a higher education institution, with a sample of 383 students from various undergraduate courses. Data collection was carried out using a structured questionnaire developed by the researcher and made available to participants via QR code. The results showed that the sample was predominantly composed of women and students affiliated with the Health Sciences Center. The most recognized area was Sports Physiotherapy. The average number of known areas varied according to the academic year, being higher among students from the Health Sciences Center. Although only 35.8% had experienced physiotherapy treatment, participants demonstrated reasonable knowledge about the presence of physiotherapists at different levels of care, especially in Primary Care, although the words cited related to the profession were linked to its rehabilitative function. Furthermore, 67.1% stated that they would seek a physiotherapist without a medical referral, indicating recognition of autonomy and direct access to the profession. It is concluded that, although students demonstrate basic knowledge about the role of the physiotherapist, significant gaps remain regarding the diversity and scope of their practice.